2008
DOI: 10.1631/jzus.b0710596
|View full text |Cite
|
Sign up to set email alerts
|

Transient expression of chicken alpha interferon gene in lettuce

Abstract: Abstract:We investigated the possibility of producing chicken alpha interferon (ChIFN-α) in transgenic plants. The cDNA encoding ChIFN-α was introduced into lettuce (Lactuca sativa L.) plants by using an agro-infiltration transient expression system. The ChIFN-α gene was correctly transcribed and translated in the lettuce plants according to RT-PCR and ELISA assays. Recombinant protein exhibited antiviral activity in vitro by inhibition of vesicular stomatitis virus (VSV) replication on chicken embryonic fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…Ngoài ra ChIFN-α được chú ý vì nó là hợp chất: có phổ hoạt động rộng (tác động lên nhiều loại virus khác nhau trên gia cầm), gần giống với các hợp chất tự nhiên, hiệu quả cao, tiện lợi khi sử dụng. Các gene mã hóa interferon alpha gà tái tổ hợp (rChIFN-α) đã lần lượt được tạo dòng, biểu hiện, và đều cho hoạt tính sinh học khi thử nghiệm in vitro và cả in vivo (Hou et al, 2011;Li, De-gang, Yong-jun, & Yi, 2008;Meng et al, 2011). Tuy nhiên, để sản xuất rChIFN-α với số lượng lớn và giá thành thấp phù hợp cho chăn nuôi thì phải cân nhắc các hệ thống biểu hiện.…”
Section: Giới Thiệuunclassified
“…Ngoài ra ChIFN-α được chú ý vì nó là hợp chất: có phổ hoạt động rộng (tác động lên nhiều loại virus khác nhau trên gia cầm), gần giống với các hợp chất tự nhiên, hiệu quả cao, tiện lợi khi sử dụng. Các gene mã hóa interferon alpha gà tái tổ hợp (rChIFN-α) đã lần lượt được tạo dòng, biểu hiện, và đều cho hoạt tính sinh học khi thử nghiệm in vitro và cả in vivo (Hou et al, 2011;Li, De-gang, Yong-jun, & Yi, 2008;Meng et al, 2011). Tuy nhiên, để sản xuất rChIFN-α với số lượng lớn và giá thành thấp phù hợp cho chăn nuôi thì phải cân nhắc các hệ thống biểu hiện.…”
Section: Giới Thiệuunclassified
“…An innovative application of ChIFN-α to antagonize AIV infection in poultry through direct oral feeding or drinking water has received more attention than other components [164,165,166,167,168]. Sekellick et al [169] showed that up to 60% of investigated AIV population belonged to the HPAI H5N9 subtype were highly sensitive to the inhibitory effects of ChIFN-α.…”
Section: Molecular Approaches For Control Of Aivmentioning
confidence: 99%
“…Nevertheless, the cost of mass production of chicken cytokines is still too high to be applied in large-scale in poultry industry [165]. Moreover, protein stability, host-specificity and labor associated with mass administration of chicken cytokines under field conditions require significant improvement [172].…”
Section: Molecular Approaches For Control Of Aivmentioning
confidence: 99%
“…The first reports about the plan-based production of human interferon date back to the beginning of the 90 s [ 56 ], however it was the usage of transplanstomic plants that allowed for the huge increase of yield, up to 20% of TSP [ 45 ]. It is worth mentioning that not only human interferons but also interferons from chicken [ 49 ] and salmon [ 50 ] were successfully produced in plant-based systems.…”
Section: Recombinant Cytokines From Plant-based Platformsmentioning
confidence: 99%